2022
DOI: 10.5534/wjmh.200184
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ejaculation and Endocrine Disorders: A Literature Review

Abstract: Premature ejaculation (PE) is the most common male sexual dysfunction, with 30% of men experiencing PE worldwide. According to the generally accepted classification, there are two types of PE: lifetime PE and acquired PE. Various biological and psychological causes are known to be involved in the etiology of PE. However, due to the incomplete definition and etiopathogenesis of PE, there is no effective treatment. Although clinical and animal studies indicate that hormones play a role in controlling the ejacula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 99 publications
(121 reference statements)
0
20
2
Order By: Relevance
“…Testosterone is considered the principal hormone involved in male gonad formation and ejaculation control. However, there are contradictory data regarding the correlation between testosterone levels and PE [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone is considered the principal hormone involved in male gonad formation and ejaculation control. However, there are contradictory data regarding the correlation between testosterone levels and PE [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The following limitations of this study should be considered. (1) The IELT used in this study was self-reported, which may lead to an overestimation, 30 and hence have lower accuracy than the stopwatch-measured IELT. (2) Although careful communication was conducted with all patients to explain the questionnaire before they filled them, it could still exist subjectivities associated with questionnaire filling.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, PE is considered as a neurobiological dysfunction that is correlated with the impairment of neurotransmission at central serotonin and 5‐HT postsynaptic receptors (Coskuner & Ozkan, 2021). Therefore, SSRIs are the main drugs recommended by ISSM for the treatment of PE (Althof et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The common AEs related with paroxetine were fatigue, yawning and abnormal sleep (10.96%), gastrointestinal upset (10.80%).F I G U R E 5Forest plots showing the intravaginal ejaculatory latency time of 20 mg paroxetine on-demand versus other treatment. CI, confidence interval; df, degrees of freedom; IV, inverse variance; SD, standard deviation Currently, PE is considered as a neurobiological dysfunction that is correlated with the impairment of neurotransmission at central serotonin and 5-HT postsynaptic receptors(Coskuner & Ozkan, 2021). Therefore, SSRIs are the main drugs recommended by ISSM…”
mentioning
confidence: 99%